(untitled) (Fiep Bulletin - online, 2014)
The aim of this study was to comprehend the teachers and students understanding on the topic of health related to obesity, realizing how or if the school comes to this matter, especially in the discipline Physical Education. The methodology was used field research, and as an instrument for data collection was the use of an interview with the students in the 3rd year of high school and the teachers of Physical Education. As a result of the research it was noticed that students understand partially what is obesity, because teachers sometimes somehow warn about the problems of obesity. It was concluded that the subject of obesity is discussed in part is relevant to working in physical education classes in school for sports activities requiring special attention in this.